The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1371/journal.pone.0195617
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of multiple mortality events in eastern box turtles (Terrapene carolina carolina)

Abstract: Wildlife mortality investigations are important for conservation, food safety, and public health; but they are infrequently reported for cryptic chelonian species. Eastern box turtles (Terrapene carolina carolina) are declining due to anthropogenic factors and disease, and while mortality investigations have been reported for captive and translocated individuals, few descriptions exist for free-living populations. We report the results of four natural mortality event investigations conducted during routine hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Immune function has not been well studied in turtles of the family Emydidae, despite their susceptibility to infectious diseases (ranavirus, Terrapene herpesvirus 1 & 2, Terrapene adenovirus, Mycoplasma sp.) that may threaten individual survival and population viability (Adamovicz et al, 2018; Johnson et al, 2008; Kane et al, 2017; Yonkers et al, 2015). Box turtles ( Terrapene spp .)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune function has not been well studied in turtles of the family Emydidae, despite their susceptibility to infectious diseases (ranavirus, Terrapene herpesvirus 1 & 2, Terrapene adenovirus, Mycoplasma sp.) that may threaten individual survival and population viability (Adamovicz et al, 2018; Johnson et al, 2008; Kane et al, 2017; Yonkers et al, 2015). Box turtles ( Terrapene spp .)…”
Section: Introductionmentioning
confidence: 99%
“…The two species also differ in habitat usage, with OBTs relying largely on prairie habitats and EBTs utilizing forested areas and adjacent fields (van Dijk, 2011; van Dijk & Hammerson, 2011). Disease‐related mortality events are reported more frequently in EBT compared to OBT, but it is unclear if this is due to differences in disease susceptibility, exposure to pathogens, or research effort (Adamovicz et al, 2018; Agha, Price, Nowakowski, Augustine, & Todd, 2017; Johnson et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This may be because transcription does not reflect true circulating cytokine concentration or the timing of sampling did not detect key changes that would improve the statistical models. Frog virus 3-like virus outbreaks in the wild have occurred in the relatively hotter months in North America of June and July [ 13 ], and mortality is likely influenced by both select host and pathogen factors. While ranavirus replication occurs across a range from 12–32°C with the highest growth at 30°C [ 6 ], the host immune response is also increased at the higher end of their preferred optimum temperature zone [ 19 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many reptile species inhabit microbe‐rich environments, such as wetlands, which are also experiencing an increase in the presence of potential pathogens due to global climate change and human needs for land and natural resources (Derne, Weinstein, & Lau, ). Recent studies have identified numerous pathogens associated with mortality events in turtles, including necrotizing bacterial infections, frog virus‐3‐like ranavirus, terrapene herpesvirus 1, adenovirus, Mycoplasma , Salmonella, and Leptospira (Adamovicz et al, ; McKenzie et al, ; Rockwell, Thompson, Maddox, & Mitchell, ). Many of these pathogens are spread by contact with mucosal surfaces; thus, an understanding of threats to turtles and conservation efforts may be enhanced with a more detailed understanding of mucosal immune protection.…”
Section: Discussionmentioning
confidence: 99%